Pengaruh Motivasi Kerja Dan Lingkungan Kerja Non Fisik Terhadap Kinerja Karyawan Pada PT. Mitra Distribusi Mandiri Cabang Sungai Pareman Makassar - Agung Pratama Salassa; Heru Sutapa; Nurali Agus Najibul Zamzam; Nur Hidayati (Universitas Katolik Widya Karya Malang, 2023)
The scope of this study focuses on work motivation (X1) and non-physical work environment (X2) variables on the dependent variable, namely employee performance (Y). The population of employees of PT. Mitra Distribusi Mandiri Sungai Pareman Branch Makassar as many as 30 people. This research uses quantitative methods.The sampling technique uses a saturated side approach. Data analysis techniques used in this study are validity and reliability test instruments, classic assumption test, multiple linear regression test, coefficient of determination, t test and F test. From the results of this study that the variable work motivation has a partially significant effect on employee performance, this can be seen from the significant t value of 0,000 < 0,05. The non-physical work environment has a partially significant effect on employee performance, this can be seen from the significant t value of 0,000 < 0,05. Simultaneously work motivation and non-physical work environment have a significant influence on employee performance, this can be seen from the significant F value of 0,000 < 0,05.